PHENOTYPE PURITY OF BALI CATTLE IN THE COASTAL AREA - Maele, Mohammad J; Yahya, Ronal; Fathan, Suparmin; Ilham, Fahrul; Laya, Nibras K; Dako, Safriyanto (Jambura Journal of Animal Science, 2024)
The role of farmer groups are very strategic in increasing the number of Bali cattle. The existence of the group has been able to increase the number of livestock. The aim of this research is to determine the phenotypic purity of Bali Cattle raised in Kabila Bone District based on Indonesia National Standards (SNI). This research was carried out in several livestock groups in Kabilabone District, Bonebolango, ± 5 months, namely in July-November 2023. Method used were visual observations and body measurements. Descriptive analysis for external phenotypic appearance and quantitative. The skin color of female Bali cattle in Molotabu and Biluango Villages experienced a shift or bias from the SNI standard of 1.67-2.85 respectively, where the body skin color was dark brown to black, while other cattle have normal colors such as brick red, brown, light brown and fawn according to SNI standards. The white color pattern on the buttocks/rump mirror (CB) is a characteristic of male and female Bali cattle. The white color is circular in shape following the shape of the rear buttocks of the Bali cattle. CB circle boundaries in Bali cattle are clearly visible. The frequency of CB color boundary phenotypes in female Bali cattle is the frequency of CB with clear boundaries was 33.33-76.67%, while those with unclear boundaries was 23.33-66.67%. The highest body weight of female Bali cattle was 262.87 while the lowest was 162.0, and the standard deviation value for body weight was ±26.10. Female Bali cattle raised traditionally do not comply with SNI standards